Faktor-Faktor yang Mempengaruhi Perilaku Konsumen Dalam Memilih Pegadaian Syariah di Kota Banjarmasin - MUBARAK, ZAKI; WINDASARI, INDRIANI (At-Taradhi, 2013)
This study intends to find out if factors including product, promotion, price, place, and service have affected consumersâ behavior in choosing syariah pawn shop (pegadaian syariah). The regression analysis results show that those factors have affected consumer decision making at 63.9%. UsingF test, all of those variables simultaneously have affected consumersâ decision in choosingsyariah pawn shop. Furthermore, using t test, only some variables including product, price, and place that partially have affected the consumersâ behavior, but, promotion and service have not affected it. The data analysis also indicates that price is the most dominant variables that affected consumersâ in choosing Syariah pawn shop.